Study of Effect of Linear Tip Relief Modification in Power Transmission Efficiency of Spur Gears - THAMBA, Narendiranath Babu; TAMBARE, Abhijeet Mukund; ANANTHANARAYANAN, Krishna Caitanya; DURAISWAMY, Rama Prabha; THANGAVELU, Shankar; EASWARA PILLAI, Raj Kumar; MANGALARAJA, Ramalinga Viswanathan (Archives of Acoustics, 2020)
This paper explores the influence of linear gear tip relief modification on power transmission efficiency. In real time applications gears experience transmission error (TE) during operation which increases noise and vibration and also results in increased tooth profile deformation during operation of the gear. By providing tip relief profile modification this TE can be decreased. Using MATLAB for computation and ANSYS for the simulation of deformation, stress, strain, life, and factor of safety results for the gear assemblies are obtained. Deformation results are used for the computation change in power transmission efficiency followed by the modal and harmonic analysis of the gears and gear assemblies to determine change in the first mode of natural frequency.